Microplastic ingestion by the sandfish Holothuria scabra in Lampung and Sumbawa, Indonesia. (February 2022) - Riani, Etty; Cordova, Muhammad Reza
Abstract: This study investigated the abundances and characteristics of microplastics in sediments and sandfish ( Holothuria scabra ) in Lampung and Sumbawa, Indonesia. Microplastics were found in 89.02% of all sandfish samples, with an average abundance of 2.01 ± 1.59 particles individual −1 . The abundance of microplastics was 58.42 ± 24.33 particles kg −1 in surface sediments. Furthermore, there was a positive relationship between the abundance of microplastics in sandfish and sediments. Fragments and fibers with small-sized microplastics (300–1000 μm) were the most abundant types found in sandfish and sediments. Fourier-transform infrared (FTIR) analysis showed that polyethylene (30.08%), polypropylene (30.08%), polyurethane (12.20%), and polyethylene terephthalate (8.94%) were the most abundant polymers in the samples. Our results strongly indicate that microplastics in Lampung and Sumbawa originate from the fragmentation of large plastics. Better solid waste management in Indonesia is needed to reduce plastic waste leakage, which could become microplastics. Highlights: Microplastics were identified in 89.02% sea cucumber and all sediment analyzed. The abundance of microplastics were 126.34 ± 51.99 particles kg −1 in sea cucumbers. The abundance of microplastics were 58.42 ± 24.33 particles kg −1 in the sediment. Moderate positive correlation between microplastics in the sediment and sea cucumbers. Microplastics found strongly suspected from the fragmentation of large plastics.